ANALISIS FAKTOR RISIKO SUMBER BAHAYA ERGONOMI TERHADAP KELUHAN GANGGUAN OTOT RANGKA EKSTREMITAS ATAS PADA PEMANEN KELAPA SAWIT DI PT RAP KALIMANTAN BARAT TAHUN 2024 - ginting, selamat; maturi, herlina J-El; andriyani, zarah beti (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Based on data from the United States Department of Labor (Accidents Facts) spinal cord injuries are one of the most common workplace accidents (22%) of all workplace accidents that occur and require the most. Of all work accidents that occur and require the most medical expenses. Complaints of Skeletal Muscle Disorders (musculoscletal) are generally in the form of pain, injury, or abnormalities in the skeletal muscular system, including nerve tissue, tendons, ligaments, muscles or joints.The type of research used is quantitative research with Cross Sectional research design. The sample in this study is the entire number of employees of PT RAP with a sample of 43 The bivariate analysis in this study is the chi square test, and the multivariate analysis uses multiple regression tests. There is a relationship between age p=0.010, work period p=0.000, work duration p=0.0001, work load p=0.001, and posture risk p=0.000, with complaints of upper extremity musculoskeletal disorders in oil palm harvesters. Multiple regression test analysis showed that body posture was p = 0.000, OR 0.005 5, CI = 0.000-0.066, which means that body posture was 0.5 times related to complaints of upper extremity musculoskeletal disorders in oil palm harvesters at PT. RAP. It is expected that the company can provide socialization to workers with the theme of occupational disease hazards and their control, so that workers can be more careful when working to avoid complaints of upper extremity skletal muscle disorders due to occupational risks.